Tax Morality Moderates Self Assessment System and Money Ethics on Tax Evasion Measures at KPP Pratama Makassar Selatan - Fahria Azhar; Tenriwaru Tenriwaru; Arifin Arifin (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
The purpose of this research is to examine the relationship between the Self Assessment System Money Ethics and Tax Morality in relation to Tax Evasion at the South Makassar Primary Tax Office. The population in this study consists of individual taxpayers registered at the South Makassar Primary Tax Office, totaling 159,626 individual taxpayers. The sample size for this study was determined using the Slovin formula, resulting in a sample of 100 taxpayers. This study employs a field research method. The statistical method used to test hypotheses involves the use of the partial least square (PLS) approach. The results of the analysis indicate that self assessment system and money ethics simultaneously have a positive and significant influence on tax evasion, while morality as a moderator weakens the impact of self assessment system and money ethics on tax evasion. Recommendations from this study include: 1) for future researchers, it is suggested to include more other independent variables that could influence tax evasion behavior. 2) future researchers are encouraged to use additional data analysis tools. 3) future studies are expected to have a broader range of respondents in their sampling.